2023
DOI: 10.1101/2023.11.28.23298693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebrovascular disease drives Alzheimer plasma biomarker concentrations in adults with Down syndrome

Natalie C. Edwards,
Patrick J. Lao,
Mohamad J. Alshikho
et al.

Abstract: ImportanceBy age 40 years over 90% of adults with Down syndrome (DS) have Alzheimer’s disease (AD) pathology and most progress to dementia. Despite having few systemic vascular risk factors, individuals with DS have elevated cerebrovascular disease (CVD) markers that track with the clinical progression of AD, suggesting a role for CVD that is hypothesized to be mediated by inflammatory factors.ObjectiveTo examine the pathways through which small vessel CVD contributes to AD-related pathophysiology and neurodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Based on previous mechanistic work, chronic exposure to soluble amyloid may impair perivascular clearance, leading to downstream amyloid deposition in the parenchyma and in the vasculature. Further, small vessel disease may be one initiator of tau phosphorylation, perhaps through an inflammatory response to damage in small vessels that upregulates kinase activity 24 , 28 , 30 . Our findings were consistent with this expected temporality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous mechanistic work, chronic exposure to soluble amyloid may impair perivascular clearance, leading to downstream amyloid deposition in the parenchyma and in the vasculature. Further, small vessel disease may be one initiator of tau phosphorylation, perhaps through an inflammatory response to damage in small vessels that upregulates kinase activity 24 , 28 , 30 . Our findings were consistent with this expected temporality.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having low rates of systemic vascular risk factors, such as hypertension, we previously showed that individuals with Down syndrome have increased magnetic resonance imaging (MRI) markers of cerebrovascular disease, including white matter hyperintensities (WMH), enlarged perivascular spaces (PVS), cerebral microbleeds, and infarcts, which increase as a function of clinical AD diagnosis and its antecedent clinical conditions 26 and may be mediated in part by inflammatory processes that result in neurodegeneration 27 , 28 . Notably, even in individuals without clinical symptoms of AD, we observed a significant degree of cerebrovascular changes, suggesting that they emerged earlier in life and may precede or coincide with the emergence of classical AD pathophysiology.…”
Section: Introductionmentioning
confidence: 99%